A Comprehensive Literature Review of Effectiveness of Vitamin D and Physical Performance and Falls in Older Adults - Erick Persson Jeffry; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Background: The effectiveness of vitamin D supplementation in enhancing physical performance and reducing falls among older adults has been a topic of considerable research and debate over the past several decades. Literature Review: Subsequent studies, such as the work by (M. Daly, 2010), further elucidated the importance of vitamin D in conjunction with exercise, highlighting that low serum 25(OH)D levels correlate with diminished muscle strength and increased fall risk. This relationship was echoed in research by (López-Torres Hidalgo, 2011), which demonstrated that combined calcium and vitamin D supplementation significantly improved musculoskeletal function and reduced falls among older adults. This points to the potential synergistic effects of these nutrients in promoting physical health. Meta-analyses, such as those conducted by (Bruyère et al., 2014) and (Rosendahl‐Riise et al., 2017), reinforced the notion that vitamin D supplementation can reduce falls and non-vertebral fractures, particularly at dosages of 700–1000 IU per day. These findings suggest a clear dose-response relationship, emphasizing the critical role of adequate vitamin D levels in maintaining muscle strength and balance, which are essential for fall prevention. However, the literature also highlights significant variability in outcomes, as noted in the systematic review by (Prokopidis et al., 2022). While some studies reported positive effects of vitamin D on muscle function, others yielded inconclusive results, pointing to the need for further research to clarify the role of vitamin D in combatting sarcopenia and its associated risks. Conclusion: In conclusion, the literature presents compelling evidence supporting the effectiveness of vitamin D supplementation in enhancing physical performance and reducing falls among older adults, particularly at higher dosages. Nonetheless, the inconsistencies in findings across various studies underscore the complexity of vitamin D's role in muscle health and fall prevention. Continued research is essential to refine supplementation strategies, address individual variability in vitamin D metabolism, and establish clear guidelines for effective interventions in older populations.